Design and manufacture of thermoplastic carbon fiber/polyethylene terephthalate composites underbody shield to protect the lithium-ion batteries for electric mobility from ground impact. (1st June 2022) - Um, Hui-Jin; Hwang, Yeon-Taek; Bae, Il-Joon; Kim, Hak-Sung
Abstract: Recently, the electric mobility has emerged with great prospects as there has been a growing interest in and demand for eco-friendly energy. The electric vehicle uses a large number of lithium batteries as sources of power, and the lithium battery poses a risk of fire and explosion when the external impact is loaded. Therefore, in this study, an underbody shield (UBS) was designed and manufactured using carbon fiber reinforced thermoplastic composites for battery protection. The underbody shield is composed of two parts, which are the main shield plate and collision protection bar (CPB). Mechanical behavior against impact was analyzed through finite element analysis considering the position of the CPB and the shape of the underbody shield plate. For the UBS, the hybrid composites (Carbon fiber (CF)/polyethylene terephthalate (PET) and self-reinforced polypropylene (SRPP) composites) were used and the ratio between the CF/PET and SRPP was optimized. Through a finite element analysis, the optimal underbody shield was designed with a thickness of 2.4 mm and a hybrid ratio of CF/PET:SRPP as 1:2. Finally, the designed underbody shield was manufactured using a thermo-forming process and mounted to an electric vehicle, and then a vehicle crash test was performed with a concrete obstacle. The developed underbody shield could protect the battery against the impact damage successfully, showing that the deformation of a rear part was within 5 mm and no battery leakage occurred.